Optimalisasi Hubungan Bisnis untuk Ekspansi Pasar Internasional UMKM Batik Giriloyo Kabupaten Bantul, Yogyakarta - Heri Prabowo; Hawik Ervina Indiworo; Qristin Violinda; Bayu Kurniawan; Ika Menarianti; Rita Meiriyanti; Fithri Widyannita Yarisma; Ratih Hesty Utami; Shofif Sobaruddin Akbar; Chadiyan Faturachman; Farah Chalida Hanoum (BADAN PENERBIT STIEPARI PRESS, 2025)
Optimizing international marketing strategies is a significant challenge faced by Micro, Small, and Medium Enterprises (MSMEs), including Batik Giriloyo business actors in Bantul Regency, Yogyakarta, in an effort to expand global market penetration. Various obstacles such as limited access to international markets, minimal use of digital technology for marketing, and weak cross-country cooperation networks are the main obstacles in business expansion. To overcome these problems, an empowerment program has been implemented which includes creating an e-commerce account through the Shopify platform and holding an international webinar entitled